Bush Meat Harvesting and Human Subsistence Nexus in the Oban Hill Communities of Nigeria (2012)
Wildlife is an important socio-cultural and economic resource in West and Central Africa. The declining wildlife population in the recent time is as a result of a combination of factors, namely, increased access and demand for wildlife resources by rural and urban dwellers, population growth, improved hunting technology and lack of protein alternatives in many households.. This paper investigates the contribution of bush meat extraction to household’s livelihood (income, health, nutrition, etc); the role of beliefs and taboos in wildlife conservation and the attitude of community members towards wildlife hunting and conservation in Oban Hills, Nigeria. Data for the study were generated through a triangulation of qualitative and quantitative methods using primary and secondary sources. It was revealed that majority of the people of Oban Hills are farmers although some also engaged in quarry business, civil service, trading, lumbering and hunting. However, there has been a decline in income generated from hunting and dependence on bush meat as protein source due to restrictions on hunting in and around forests in the protected area. It was also observed that beliefs and taboos in form of totems played a major role in wildlife conservation in the past; therefore involving existing cultural institutions in conservation efforts will facilitate sustainable wildlife exploitation in Oban Hills. However, the involvement of the cultural institution in the conservation agenda and the integration of these values into the overall conservation strategy will be achieved through a formal process of recognition and consultation by the responsible government agencies